THE PUBLIC SPHERE OF POLITICS: THE ANTHROPOLOGICAL DIMENSION IN CONTEMPORARY COMMUNICATIVE THEORY - O. A. Tretyak (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Introduction. According to Jürgen Habermas, a contradiction between the system and the life-world signifies a need for a concept that would describe the projective space of a relaxed and undistorted human communicative activity. Communicative action as a societal basis of the public sphere links this concept to the pragmatic principles of human existence in modern society. The public sphere is important in the age of the cyber revolution and the rule of networking technologies and it gets an anthropological dimension in its definition of the modern individual. Reviewed from the view of the interdisciplinary scientific community the public sphere as a dimension of human identity that is manifested in standardized terms of communicative interactions. The paper suggests that the public sphere has lost its conflict mode in respect to power and the tech-savvy social system. Purpose. The paper aims to establish the specifics of the anthropological interpretation of the public sphere in the contemporary philosophical tradition. Methodology. General scientific and special methods of philosophical research are used for conducting this study. The author has used the descriptive method to define the subject area of the anthropic measurement of the public sphere of politics. The method of logical synthesis allows to combine the abstract and specific content of the anthropological dimension of publicity. A retrospective analysis allows to determine the temporal peculiarities of the anthropic meaning of the public sphere. The comparative method gives an opportunity to compare the empirical manifestations of social and political publicity and compare anthropological effects of the media and interpersonal communication activities of modern people. Theoretical basis and results. The article examines the anthropological content of the public sphere of politics as one of the key concepts of communicative theory paying attention to the modification of the nature of publicity under the conditions of the cybernetic revolution. The author argues that the public sphere is not only a collection of self-presentations but also a set of messages of general significance, both textual and verbal. In this regard, the selection of news, of any importance, stands in one respect as a means of the worldview matching technique but also as the orientation amidst the unlimited information flow. The public sphere acts not just as a medium of verbal or textual self-expression of the individual but also as a dimension of human presence in the lives of others and its adequate perception. The more the public sphere stands away from the counter-factual image drawn in communicative theory, the more it loses its anthropological features and acquires the content of the technological and production network since a mode of communication is changed to the mode of information transmission. The paper establishes priorities of personality representation in the public sphere and examines the need and motives of communicative-pragmatic relationships between individuals. Originality. In the anthropological dimension the public sphere is a source of promising prospects and the formation of defining constraints. Publicity becomes the leading quality of the modern individual because of its need to be realized in communication practices. The networking nature of communication links enforces the modern individual to produce a certain image for self-presenting to society. Conclusions The article draws a conclusion about the directions of the public sphere transformation in a global perspective.